C-DC and MC-DC Casting of Al-alloys-A Comsol Approach - Walinjkar, Devavrat; A. K., Prasada Rao (Elsevier B.V., 2015)
Present work endeavours to understand the solidification behaviour in conventional direct chill casting (C-DC) of aluminium alloy billets. The simulations were generated for C-DC and MC-DC (melt-conditioned) processes. For the first time, COMSOL Multiphysics has been successfully used to simulate the heat flow in C-DC casting of Al-alloy billet. The results show that the temperature gradient in the sump is minimized in the case of MC-DC when compared with C-DC. The simulation results also revealed the effect of casting speed on the sump profile in both the cases.